Proteomelevel change in the roots of Pisum sativum L. in response to salinity - Kav, N.N.; Srivastava, S.; Goonewardene, L.; Blade, S.F. (Wiley, 2004)
We initiated a proteomics-based approach to identify root proteins affected by salinity in pea (Pisum sativum cv. Cutlass). Salinity stress was imposed either on 2-wk old pea plants by watering with salt water over 6 wk or by germinating and growing pea seeds for 7 days in Petri dishes. Concentrations of NaCl above 75 mM had significant negative effects on growth and development of peas in both systems. Salinity-induced root proteome-level changes in pea were investigated by 2-D electrophoresis of proteins from control, 75 and 150 mM NaCl-treated plants and seedlings. The majority of the protein spots visualised showed reproducible abundance in root protein extracts from whole plants and seedlings. Of these proteins, 35 spots that exhibited significant changes in abundance due to NaCl treatment were selected for identification using ESI-Q-TOF MS/MS. The identities of these proteins, which include pathogenesis-related (PR) 10 proteins, antioxidant enzymes such as superoxide dismutase (SOD) as well as nucleoside diphosphate kinase (NDPK) are presented, and the roles of some of them in mediating responses of pea to salinity are discussed. This is the first report of salinity-induced changes in the root proteome of pea that suggests a potential role for PR10 proteins in salinity stress responses. Our findings also suggest the possible existence of a novel signal transduction pathway involving SOD, H2O2, NDPK and PR10 proteins with a potentially crucial role in abiotic stress responses.